2016
DOI: 10.15763/issn.2376-5275.2015.1.2.31-63
|View full text |Cite
|
Sign up to set email alerts
|

From Bootstraps to Hands-up: A Multicultural Content Analysis of The Depiction of Poverty in Young Adult Literature

Abstract: <p>This article describes the findings of a qualitative critical multicultural content analysis of 71 young adult (YA) novels depicting poverty and published between 1996 when the Personal Responsibility and Work Opportunity Reconciliation Act (PRWORA) was signed into law by President Bill Clinton and 2013. The study answers three research questions: In what ways does YA literature published after the PRWORA portray poverty? How do those representations compare to current statistics regarding poverty in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Recent scholarship has examined depictions of constructs in contemporary YA literature, such as identity construction of Black immigrant youth (Omogun & Skerrett, 2021); dominant beliefs about Black girls across the African diaspora (Brooks & Cueto, 2018); queer elements and ideologies (Blackburn et al, 2015); and depictions of poverty (Hill & Darragh, 2016). Following in these researchers’ scholarly footsteps, we undertook a critical textual analysis of a selection of YA books focusing on a different underrepresented population—working-class youth in rural Appalachia—to understand how the political and cultural structures of their communities have influenced and shaped the identity construction and movement of the characters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent scholarship has examined depictions of constructs in contemporary YA literature, such as identity construction of Black immigrant youth (Omogun & Skerrett, 2021); dominant beliefs about Black girls across the African diaspora (Brooks & Cueto, 2018); queer elements and ideologies (Blackburn et al, 2015); and depictions of poverty (Hill & Darragh, 2016). Following in these researchers’ scholarly footsteps, we undertook a critical textual analysis of a selection of YA books focusing on a different underrepresented population—working-class youth in rural Appalachia—to understand how the political and cultural structures of their communities have influenced and shaped the identity construction and movement of the characters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We did find one content analysis that peripherally addressed addiction as a topic that appears in YAL connected to poverty. In their content analysis, Crag Hill & Janine Darragh ( 2016 , p. 42) found that across their sample of texts, 37.8% of the “books portrayed a character with some sort of …drug addiction.” This tells us that addiction appears in YAL texts with measurable frequency, but Hill & Darragh’s study was not primarily focused on experiences of addiction and thus offered no critical analysis of portrayals of addiction. Finally, Meagan Lacy ( 2015 ) conducted a literary analysis of children’s books about experiences of children of alcoholics.…”
Section: Introductionmentioning
confidence: 99%
“…This same power necessarily leads to concerns about how various topics are covered in books which teens may read without the intermediary of a teacher or parent. Hence we have studies of young adult fiction concerning the portrayal of adoption (Parsons, Fuxa, Kander, & Hardy, 2017), African Americans (Brooks, 2006; Smith, 1994), LGBTQ (lesbian, gay, bisexual, transgender, queer) content (Cart & Jenkins, 2006; Jenkins, 1998), weight (Glessner, Hoover, & Hazlett, 2006), poverty (Hill & Darragh, 2016), “geeks and nerds” (Stanley, 2015), and female sexuality (Younger, 2003) among other topics. 3 In their analysis of LGBTQ themes in YAL, Cart and Jenkins (2006, pp.…”
Section: Introductionmentioning
confidence: 99%